Mengenal Konsep Wujud Dalam Filsafat Mulla Sadra (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2017)
This paper will specifically discusses the concept of wujud in the al-hikmah al-muta'aliyah of Mulla Sadra. Mulla Sadra's thought has been widely studied among intellectuals, traditional madrassahs and modern universities. This shows that the intellectual tradition in Islam is in fact always evolving and is alive up to these days. It did not cease in Ibn Rushd's era, as it was understood by many partieslearned in the West.The study aims to find, discover and show the excellence of al-hikmah al-muta'aliyahof Mulla Sadra among the earlier Islamic thinkers, and then analyzes its important implications for the history of Islamic thought in general, and for Islamic philosophy in particular. The result shows that al-hikmah al-muta'aliyah is one of genres in the history of Islamic thought which has a unique characteristic that is trying to integrate two previous genres, the peripatetic and illumination genres. Mulla Sadra's formulation of the philosophy of wujud is based on three fundamental principles, namely ashalatul wujud, Tasykik wujud and causality.